2010
DOI: 10.3892/or_00000898
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of Annexin A10 in gastric cancer and its overexpression in tumor cell growth suppression

Abstract: Abstract. Gastric carcinoma is the most common neoplasm in Southeast Asian populations and is the second leading cause of cancer death worldwide. Annexins are a family of cytosolic calcium and membrane binding proteins that have been implicated in a wide variety of cell functions. Recent studies have suggested that Annexin A10 (ANXA10), a member of the Annexin protein family, is down-regulated in specific types of cancer. However, the underlying molecular mechanisms of the dysregulation of ANXA10 remain to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Several studies have identified ANXA10 as a tumor suppressor, diagnostic marker, potential therapeutic target, or prognostic factor in various malignancies, including bladder cancer, hepatocellular carcinoma, acute myeloid leukemia, gastric carcinoma, oral squamous cell carcinoma, pancreatobiliary adenocarcinoma, and urothelial carcinoma [33,34,35,36,37]. Studies have shown that ANXA10 was down-regulated in hepatocellular carcinoma and was associated with a poor prognosis [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified ANXA10 as a tumor suppressor, diagnostic marker, potential therapeutic target, or prognostic factor in various malignancies, including bladder cancer, hepatocellular carcinoma, acute myeloid leukemia, gastric carcinoma, oral squamous cell carcinoma, pancreatobiliary adenocarcinoma, and urothelial carcinoma [33,34,35,36,37]. Studies have shown that ANXA10 was down-regulated in hepatocellular carcinoma and was associated with a poor prognosis [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are ongoing to establish the pathogenic roles of these proteins in the progression of squamous cell carcinomas of the head and neck and especially, to determine whether their altered expression is a cause or consequence of the cancerous state. The association of ANXA9 with pathogenic prognosis in colorectal cancer [13] contrasts with a proposed tumor suppressor role for ANXA10 in gastric cancer [36]. The unique, calcium-independent actions of these two annexins may also contribute to a better understanding of their underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Ishikawa, A. et al, KRT80 was suggested to be potentially associated with the ANXA10 regulatory pathway in GC, and ANXA10 knockdown was able to increase the proliferation 25,39 and invasiveness 40 of GC cell lines as well as their sensitivity to 5-FU. 41 GC has contributed to much of the research on KRT80 in cancer.…”
Section: Krt80 and Gastric Cancer (Gc)mentioning
confidence: 99%
“…A recent study from Japan reported that the loss of ANXA10 expression was detected in 61.2% of early GC patients and also significantly associated with poor OS [113]. ANXA10 may affect the development of GC by inhibiting the malignant phenotype [114]. When an ANXA10 overexpressing plasmid was introduced into MKN-1 GC cells, the cell growth was suppressed, and apoptosis was augmented [114].…”
Section: Structure and Function Of Annexin A Familymentioning
confidence: 99%
“…ANXA10 may affect the development of GC by inhibiting the malignant phenotype [114]. When an ANXA10 overexpressing plasmid was introduced into MKN-1 GC cells, the cell growth was suppressed, and apoptosis was augmented [114]. In addition, ANXA10 was also involved in the induction of pancreatic duodenal homeobox 1(PDX1) expression in GC [112].…”
Section: Structure and Function Of Annexin A Familymentioning
confidence: 99%